Patterns of source monitoring bias in incarcerated youths with and without conduct problems. Issue 1 (2nd January 2018) - Morosan, Larisa; Badoud, Deborah; Salaminios, George; Eliez, Stephan; Van der Linden, Martial; Heller, Patrick; Debbané, Martin
ABSTRACT: Introduction: Antisocial individuals present behaviours that violate the social norms and the rights of others. In the present study, we examine whether biases in monitoring the self-generated cognitive material might be linked to antisocial manifestations during adolescence. We further examine the association with psychopathic traits and conduct problems (CPs). Methods: Sixty-five incarcerated adolescents (IAs; M age = 15.85, SD  = 1.30) and 88 community adolescents (CAs; M age = 15.78, SD  = 1.60) participated in our study. In the IA group, 28 adolescents presented CPs ( M age = 16.06, SD  = 1.41) and 19 did not meet the diagnostic criteria for CPs ( M age = 15.97, SD  = 1.20). Source monitoring was assessed through a speech-monitoring task, using items requiring different levels of cognitive effort; recognition and source-monitoring bias scores (internalising and externalising biases) were calculated. Results: Between-group comparisons indicate greater overall biases and different patterns of biases in the source monitoring. IA participants manifest a greater externalising bias, whereas CA participants present a greater internalising bias. In addition, IA with CPs present different patterns of item recognition. Conclusions: These results indicate that the two groups of adolescents present different types of source-monitoring bias for self-generated speech. In addition, the IAs with CPs present impairments in item recognition. Future studies may examine the developmental implications of self-monitoring biases in the perseverance of antisocial behaviours from adolescence to adulthood.